Quantifying the largest aggregation of giant trevally Caranx ignobilis (Carangidae) on record: implications for management. Issue 3 (3rd July 2018) - Daly, R; Daly, CAK; Bennett, RH; Cowley, PD; Pereira, MAM; Filmalter, JD
Abstract : The giant trevally Caranx ignobilis (Forsskål) is an important apex predatory fish typically associated with coral reef communities. It is prized in recreational and commercial fisheries, yet little is known about its aggregation dynamics and susceptibility to fishing pressure. This study reports on a previously undocumented aggregation of mature giant trevally observed over a period of eight years (2010–2017) at Ponta do Ouro Partial Marine Reserve in southern Mozambique. The aggregation is one of the few recorded for this carangid in the western Indian Ocean and represents the first subtropical aggregation of giant trevally. The aggregation is also the largest recorded for this species, with up to 2 413 individuals representing an estimated biomass of approximately 30 tonnes. The size and predictability of this annual aggregation make it vulnerable to overexploitation and point towards the need for an appropriate conservation management strategy.